Synthesis and characterization of S-Scheme NiMn2O4/g-C3N4 nanocomposites heterojunction photocatalyst for effective degradation of organic pollutants under visible light - Masoumeh Yaqoubi; Mojgan Ghanbari; Rana Warid Maya; Hassan Abdulhadi Jasim; Masoud Salavati-Niasari (Results in Engineering)
This work reports the first steps in the preparation of nickel manganese oxide (NiMn2O4) using an inexpensive and straightforward co-precipitation approach. Next, NiMn2O4/g-C3N4 heterostructure with varying mass ratios are made using an ultrasonic-assisted co-precipitation process. Many methods, including XRD, FTIR, EDS, SEM, TEM, BET, VSM, and DRS, were used to characterize NiMn2O4 and its nanocomposites. The photocatalytic activity of NiMn2O4, g-C3N4, and various NiMn2O4/g-C3N4 nanocomposites was studied for the degradation of eriochrome black T (EB). This is the first time that NiMn2O4 has been coupled with carbon nitride, demonstrating outstanding photocatalytic efficiency. The results showed that numerous factors influenced efficiency, including NiMn2O4 content, catalyst content, and EB concentration. 1 %NiMn2O4/g-C3N4 has the highest performance, which 30 mg of 1 %NiMn2O4/g-C3N4 to degrade 96.41 % of 10 ppm EB in the acidic media. The scavenger experiments revealed that superoxide radicals played an important part in the photodegradation events. The kinetics investigation found that a higher rate constant (k = 0.0241 min‒1) corresponded to better efficiency (96.41 %).